Distribución y abundancia de las especies de peces típicas en el sistema arrecifal de Akumal, Caribe Mexicano: relaciones peces-hábitat - Alva Basurto, Jorge Christian (Universidad Autónoma Metropolitana, 2007)
The high diversity of coral reef fishes makes complex the problem of its evaluation at ecosystem level. One of the strategies that allow knowing these communities to a scale of smaller complexity is to detect to the typical species whose ecological parameters (i. e. density, appearance frequency, distribution) they prevail in the structure of the community. The analysis of typical populations makes more accessible the interpretation of the ecology of the system. Understanding like these species work it allows analyzing the behavior of other species, establishing the main patterns of the community in relation to the environmental characteristics, their seasonal variations and the interactions fishes/habitat. They were carried out visual censuses in the coral reef of Akumal, Quintana Roo, Mexico. With the index of Total Relative Importance (TRI) 12 typical species belonging to five families were obtained (Teleostei: Acanthuridae, Haemulidae, Labridae, Pomacentridae, Scaridae), with 20, 457 individuals, representing 65.16% of the total number of individuals reported for the system. These species are: Abudefduf saxatillis, Acanthurus bahianus, A. chirurgus, A. coeruleus, Haemulon flavolineatum, H. sciurus, Halichoeres radiatus, Microspathodon chrysurus, Scarus taeniopterus, Sparisoma viride, Stegastes adustus and Thalassoma bifasciatum. Each one of the typical species presents distribution patterns and own abundance, however on the whole and in an annual way, they present corresponding rules mainly to the habitats of the lagoon, fore reef slope and area of Yal-Kú. Differences exist among the abundances of the typical species during the three climatic times, that which indicates a seasonal and space change depending on the time of the year, being in north where the distribution and abundance is more homogeneous in the whole reef. The species of the family Acanthuridae presents the biggest abundances in the reef flat and reef slope, being A. chirurgus the most abundant species in all the typical species with 2,664 individuals. The most important factor that influences in the distribution and abundance of the typical species of coral reef fishes is the coralline covering.; La alta diversidad de peces arrecifales coralinos hace complejo el problema de su evaluación a nivel de ecosistema. Una de las estrategias que permite conocer estas comunidades a una escala de menor complejidad, es detectar a las especies típicas cuyos parámetros ecológicos (i. e. densidad, frecuencia de aparición, distribución) predominan en la estructura de la comunidad. El análisis de poblaciones típicas hace más accesible la interpretación de la ecología del sistema. El comprender como funcionan estas especies permite analizar el comportamiento de otras especies, estableciendo los principales patrones de la comunidad en relación a las características ambientales, sus variaciones estacionales y las interacciones peces/hábitat. Se realizaron censos visuales en el arrecife coralino de Akumal, Quintana Roo, México. Con el índice de Importancia Relativa Total (IRT) se obtuvieron 12 especies típicas pertenecientes a cinco familias (Teleostei: Acanthuridae, Haemulidae, Labridae, Pomacentridae, Scaridae), con 20, 457 individuos, representando el 65.16 % del número total de individuos reportados para el sistema. Estas especies son: Abudefduf saxatillis, Acanthurus bahianus, A. chirurgus, A. coeruleus, Haemulon flavolineatum, H. sciurus, Halichoeres radiatus, Microspathodon chrysurus, Scarus taeniopterus, Sparisoma viride, Stegastes adustus y Thalassoma bifasciatum. Cada una de las especies típicas presentan patrones de distribución y abundancia propios, sin embargo en conjunto y de manera anual, presentan pautas correspondientes principalmente a los hábitats de la laguna, parte anterior arrecifal y zona de Yal-Kú. Existen diferencias entre las abundancias de las especies típicas durante las tres épocas climáticas, lo cual indica un cambio estacional y espacial dependiendo de la época del año, siendo en nortes donde la distribución y abundancia es más homogénea en todo el arrecife. Las especies de la familia Acanthuridae presentan las mayores abundancias en la parte posterior y frente arrecifal, siendo A. chirurgus la especie más abundante de todas las especies típicas con 2,664 individuos. El factor más importante que influye en la distribución y abundancia de las especies de peces arrecifales coralinos típicos es la cobertura coralina.